APAKAH AGRESIVITAS PAJAK MENURUNKAN TINGKAT KEINFORMATIFAN LABA PERUSAHAAN? - Pria Aji Pamungkas; Amrie Firmansyah (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract— This research aims to examine the association between tax aggressiveness and the level of earnings informativeness. This study examines whether tax aggressiveness is being responded to by the market. This study's methodology is a quantitative approach with multiple linear regression models and panel data. The sample employed in this study is trading sector companies listed on the Indonesia Stock Exchange (IDX). The type of data used in this study is secondary data sourced from financial statements, stock price information, and annual reports from 2017 to 2019. The sample selection using a purposive sampling method with the number of samples amounted to 48 firm-year. This study suggests that tax aggressiveness is negatively associated with the level of earnings informativeness. The complexity of the company's tax aggressiveness activities makes it more difficult for investors to understand the quality of earnings reported by the company. Keywords: Tax Aggressiveness; Tax Avoidance; Earnings Informativeness; ERC; Market Responsiveness